Doctrine, practice, and advocacy in the Inter-American human rights system - Cavallaro, James; Vargas, Claret; Sandoval Villalba, Clara; Duhaime, Bernard; e uthor; Brewer, Stephanie Erin; e uthor; Naddeo, Cecilia Cristina (New York, NY : Oxford University Press, 2019)
"[This book focuses] on the inter-American human rights system, the primary system for advancing and protecting rights in the Western hemisphere. Created by the Organization of American States, the Inter-American Commission on Human Rights and the Inter-American Court of Human Rights are autonomous and independent bodies that make up the inter-American system. Together, they play a vital role, working closely with victims, civil society, and states to protect fundamental human rights in the Western hemisphere, particularly in Latin America. While the system is relatively unknown in legal academia in the United States and Canada, its study is mandatory in most law schools in the Americas. Government appointees, civil servants, high level actors, private attorneys, judges and legal scholars, and media regularly engage with the system in Latin America, implementing its determinations and applying its rulings and interpretations concerning the human rights of their citizens. Thus critical matters affecting vital rights, such as the peace process in Colombia, disappearances in Mexico, gang violence in the Northern Triangle (El Salvador, Honduras, and Guatemala) or trials for perpetrators of crimes against humanity in Argentina, all directly involve the rulings and actors of the Inter-American system. Increasingly, the inter-American system has advanced rights protection in the United States and Canada. The statements and determinations of the Inter-American Commission on the detention center at Guantanamo, for example, led to a global consensus opposing the prolonged use of pretrial detention at that site, while the Commission's ruling on the juvenile death penalty was cited by the United States Supreme Court in its holding finding that practice unconstitutional. A report by the Commission on murdered and missing indigenous women in British Columbia led to the creation of a National Commission of Inquiry on the subject by Canada. This book provides analysis on a wide range of practical issues that advocates face when interacting with the Commission or Court and explores current debates on possible reforms of the system. At the same time, it provides materials that consider the political dynamics that empower and constrain the system. [This book] takes as its point of departure a critical look at the real-world successes and failures of the system and human rights advocates in the Americas, including the tensions and trade-offs commonly confronted by activists as they seek to advance human rights."--
Introduction: Doctrine, practice, and advocacy in the Inter-American human rights system -- Evolution of the system : the Inter-American Commission and Court -- Petitioning the Inter-American system : admissibility requirements for contentious cases -- Jurisdiction beyond contentious cases : what else can the system do? -- Mass atrocity, contemporary responses and transitional justice -- The right to life -- Emergency, armed conflict, and human rights protections in the Inter-American system -- Detention and conditions in detention centers -- The rights to physical integrity, freedom from torture, and freedom from third-party violence -- Women's rights, gender, and sexuality -- The rights of children -- Indigenous and tribal peoples' rights and the Inter-American system -- Freedoms of belief, expression, assembly, and association -- Economic, social, and cultural rights -- Reparations and compliance -- The future of the Inter-American human rights system.
Includes bibliographical references and index.
Keywords: Inter-American Commission on Human Rights; Inter-American Court of Human Rights; Inter-American Commission on Human Rights; Inter-American Court of Human Rights; Human rights -- America; Human rights; Americas; Human rights; Inter-American Court of Human Rights; Inter-American Commission on Human Rights; America